RADI-09. Clinical factors associated with death after radiotherapy for brain metastases. (9th August 2021) - Natesan, Divya; Carpenter, David; Giles, William; Oyekunle, Taofik; Niedzwiecki, Donna; Reitman, Zachary; Kirkpatrick, John; Floyd, Scott
Abstract: Introduction: It can be challenging to accurately identify patients with brain metastases who have very poor prognosis and are unlikely to benefit from radiation (RT). We characterized factors of patients who died within 30 days of receiving RT for brain metastases. Methods: Patients who received whole brain RT (WBRT) or stereotactic radiosurgery (SRS) for brain metastases between 1/1/2017–9/30/2020 at a single institution were identified. Patient, tumor, treatment, and death variables were collected. Characteristics between those who did and did not die within 30 days were compared using the Wilcoxon Rank-Sum or Chi-Square test. Survival was estimated with Kaplan-Meier method. Results: 636 patients received WBRT (n=117) or SRS (n=519). Median age was 61. Median survival was 6 months (95% CI 5–7 months). 75 (12%) died within 30 days of RT. Patients who died within 30 days had worse median KPS (50 vs 80, p<0.001). A higher proportion who died within 30 days had innumerable intracranial metastases (45% vs 11%, p<0.001), leptomeningeal disease (16% vs 5%, p<0.001), and higher burden of neurologic symptoms at presentation (seizures (12% vs 4%, p=0.003); cranial neuropathies (32% vs 9%, p<0.001); motor/sensory deficits (51% vs 29%, p<0.001); altered mentation (60% vs 26%, p<0.001); headaches (48% vs 30%, p<0.001); steroid use (68% vs 48%, p<0.001)). Patients who died within 30 days had progressive extracranial disease (intrathoracic: 87% vs 50%; spinal: 57% vs 18%; liver/adrenal: 60% vs 24%), p<0.001. More patients who died within 30 days received inpatient RT (39% vs 4%, <0.001) and did not complete RT (24% vs 1%, p<0.001). Discussion: Patients who died within 30 days of RT had worse KPS, intracranial/extracranial disease burden, and neurologic symptoms. Future analyses will assess whether these factors can inform a prognostic model to identify patients with poor prognosis who may be appropriate for supportive care alone.